A possibilidade de admissão de provas ilícitas no processo penal brasileiro - Fernandes, Joel de Oliveira (2015)
The aim of this work is to analyze the admission possibility of illegal evidence in the brazilian criminal proceedings, especially regarding the use of illegal evidence pro societate. Thus, it was first necessary to define the concept of evidence, its object and purpose. They were also analyzed aspects of the evidentiary prohibition contained in art. 5, item LVI of the Federal Constitution, the legal principles involved and theories related to illegal evidence shunt, especially the theory of the fruits of the poisonous tree. Then it sought to establish the principle of proportionality (Balancing test) as exclusionary rule the inadmissibility of illegal evidence. Finally it was analyzed concrete cases for the better understanding of the theme, ending with the proposition of new admissions possibilities of illegal evidence in favor of society. The methodology used in the preparation of this work was based fundamentally on documentary and bibliographical research, in addiction to legislative review.